The genome sequence of the European ground squirrel, Spermophilus citellus (Linnaeus, 1766) [version 1; peer review: 2 approved, 1 approved with reservations] - Dionisios Youlatos; Dimitra-Lida Rammou; Alexandros Triantafyllidis (Wellcome Open Research)
We present a genome assembly from a female Spermophilus citellus (European ground squirrel; Chordata; Mammalia; Rodentia; Sciuridae). The genome sequence has a total length of 3,090.03 megabases. Most of the assembly (95.47%) is scaffolded into 20 chromosomal pseudomolecules, including the X sex chromosome. The mitochondrial genome has also been assembled, with a length of 16.45 kilobases.